Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams. (15th December 2020) - Nagler, Magdalena; Praeg, Nadine; Niedrist, Georg H.; Attermeyer, Katrin; Catalán, Núria; Pilotto, Francesca; Gutmann Roberts, Catherine; Bors, Christoph; Fenoglio, Stefano; Colls, Miriam; Cauvy‐Fraunié, Sophie; Doyle, Brian; et al.
Abstract: Aim: Although running waters are getting recognized as important methane sources, large‐scale geographical patterns of microorganisms controlling the net methane balance of streams are still unknown. Here we aim at describing community compositions of methanogenic and methanotrophic microorganisms at large spatial scales and at linking their abundances to potential sediment methane production (PMP) and oxidation rates (PMO). Location: The study spans across 16 European streams from northern Spain to northern Sweden and from western Ireland to western Bulgaria. Taxon: Methanogenic archaea and methane‐oxidizing microorganisms. Methods: To provide a geographical overview of both groups in a single approach, microbial communities and abundances were investigated via 16S rRNA gene sequencing, extracting relevant OTUs based on literature; both groups were quantified via quantitative PCR targeting mcrA and pmoA genes and studied in relation to environmental parameters, sediment PMP and PMO, and land use. Results: Diversity of methanogenic archaea was higher in warmer streams and of methanotrophic communities in southern sampling sites and in larger streams. Anthropogenically altered, warm and oxygen‐poor streams were dominated by the highly efficient methanogenic families Methanospirillaceae, Methanosarcinaceae and Methanobacteriaceae, but did not harbour any specific methanotrophic organisms. Contrastingly, sediment communities in colder, oxygen‐rich waters with little anthropogenic impact were characterized by methanogenic Methanosaetaceae, Methanocellaceae and Methanoflorentaceae and methanotrophic Methylococcaceae and Cd . Methanoperedens. Representatives of the methanotrophic Crenotrichaceae and Methylococcaceae as well as the methanogenic Methanoregulaceae were characteristic for environments with larger catchment area and higher discharge. PMP increased with increasing abundance of methanogenic archaea, while PMO rates did not show correlations with abundances of methane‐oxidizing bacteria. Main conclusions: Methanogenic and methanotrophic communities grouping into three habitat types suggest that future climate‐ and land use changes may influence the prevailing microbes involved in the large‐scale stream‐related methane cycle, favouring the growth of highly efficient hydrogenotrophic methane producers. Based on these results, we expect global change effect on PMP rates to especially impact rivers adjacent to anthropogenically disturbed land uses.